The Safety of Bacteriophages in Treatment of Diseases Caused by Multidrug-Resistant Bacteria - Ka Mun Chung; Sue C. Nang; Swee Seong Tang (MDPI AG, 2023)
Given the urgency due to the rapid emergence of multidrug-resistant (MDR) bacteria, bacteriophages (phages), which are viruses that specifically target and kill bacteria, are rising as a potential alternative to antibiotics. In recent years, researchers have begun to elucidate the safety aspects of phage therapy with the aim of ensuring safe and effective clinical applications. While phage therapy has generally been demonstrated to be safe and tolerable among animals and humans, the current research on phage safety monitoring lacks sufficient and consistent data. This emphasizes the critical need for a standardized phage safety assessment to ensure a more reliable evaluation of its safety profile. Therefore, this review aims to bridge the knowledge gap concerning phage safety for treating MDR bacterial infections by covering various aspects involving phage applications, including phage preparation, administration, and the implications for human health and the environment.